2015
DOI: 10.1152/ajpheart.00615.2015
|View full text |Cite
|
Sign up to set email alerts
|

Persistent change in cardiac fibroblast physiology after transient ACE inhibition

Abstract: Transient angiotensin-converting enzyme (ACE) inhibition induces persistent changes that protect against future nitric oxide synthase (NOS) inhibitor-induced cardiac fibrosis and inflammation. Given the role of fibroblasts in mediating these effects, the present study investigates whether prior ACE inhibition produced persistent changes in cardiac fibroblast physiology. Adult male spontaneously hypertensive rats (SHRs) were treated with vehicle (C+L) or the ACE inhibitor, enalapril (E+L) for 2 wk followed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Deijanera et al ( 75 ) demonstrated the ACEIs have an effect on reducing TGF-β1, TGF-β2, and Th2 cytokines. ACEIs also induce the apoptosis of cardiac fibroblasts ( 76 ). A clinical trial from Maskito et al ( 77 ) showed the reduction of sST2 in heart failure patients.…”
Section: The Role Of Aceis In Cardiac Fibrosis In Rhdmentioning
confidence: 99%
“…Deijanera et al ( 75 ) demonstrated the ACEIs have an effect on reducing TGF-β1, TGF-β2, and Th2 cytokines. ACEIs also induce the apoptosis of cardiac fibroblasts ( 76 ). A clinical trial from Maskito et al ( 77 ) showed the reduction of sST2 in heart failure patients.…”
Section: The Role Of Aceis In Cardiac Fibrosis In Rhdmentioning
confidence: 99%
“…Further support of this comes from recent data from D'Souza et al, who demonstrate reduced activation in CFs isolated from rats treated with ACE inhibitors. One proposed mechanism is apoptosis of activation-prone CFs and survival of more quiescent CFs [179, 180]. These data suggest that a subpopulation of CFs may retain the ability to revert back into a quiescent state or undergo apoptosis.…”
Section: Fibroblast Resolution and Reprogrammingmentioning
confidence: 99%
“…In this study, phillyrin showed effects similar to those of enalapril, further indicating that phillyrin might be a new type of anti-CF agent. Further, in this study, phillyrin was predicted to regulate many genes, including collagen genes, fibrillin, serpin family proteins, laminin, and lysyl oxidase, which are closely related to both fibrosis and inflammation (Van der Donckt et al, 2015;Jeong et al, 2018;Pastel et al, 2018;Choi et al, 2019;Leal-Lopes et al, 2019).…”
Section: Phillyrin Improved the Heart Function And Attenuated The Fibmentioning
confidence: 72%
“…This study focused on the antifibrotic effect of phillyrin. Enalapril which has an antifibrotic effect was selected as the control medicine in this study ( D’Souza et al., 2015 ; Ham et al., 2018 ). The antifibrotic effect of phillyrin was predicted based on its transcriptional profiles, which was further experimentally validated using animal models.…”
Section: Introductionmentioning
confidence: 99%